Kadar Kolesterol Kuning Telur Ayam Ras pada Peternakan Ayam yang Berbeda: Cholesterol Levels of Egg Yolks at Different Chicken Farms - Yope Y. Ohoilulin; Tabita N. Ralahalu; Dominggus Malle (Fakultas Peternakan Universitas Papua, 2023)
Abstract This study aims to determine the cholesterol levels of layer egg yolks produced by several farms in the island of Ambon. The research was conducted in Ambon Island, in three villages, namely: Suli village, Rumah Tiga village (Taeno village), and Hunuth village (Hulung village), for 1 month. The tools used in this study include: digital scales, egg tray, cellphone camera, stationery. The material used was Lohman Brown strain chicken eggs from 6 months old hen. The research was carried out descriptively, and data were collected to obtain information regarding the management of feeding, general maintenance, and feed consumption. The variables observed in this study including main variable (egg yolks) and supporting variables. The nutritional value of the feed was analyzed using the proximate technique. The results showed that cholesterol levels in several laying hens farms on Ambon Island were 547.41 mg/100g in Suli village, 543,26 mg/100g in Hulung hamlet, and 539,91 mg/100g in Taeno hamlet. Based on the study´s results, it was concluded that the lowest broiler chicken egg yolk cholesterol levels were found in Taeno hamlet chicken farms at 539.909mg/100g. Keywords: Cholesterol; Egg yolk; Laying hens Abstrak Penelitian ini bertujuan untuk mengetahui kadar kolesterol kuning telur ayam ras yang diproduksi oleh beberapa peternakan di Pulau Ambon. Penelitian dilakukan di Pulau Ambon, pada tiga desa yaitu: Desa Suli, Rumah tiga (Dusun Taeno), dan Hunuth (Dusun Hulung), selama 1 bulan. Alat yang digunakan dalam penelitian ini antara lain: timbangan digital, egg tray, kamera Android, alat tulis-menulis. Bahan yang digunakan adalah telur ayam strain Lohman Brown dari induk ayam berumur 6 bulan. Penelitian dilakukan secara deskriptif serta dilakukan pengambilan data untuk memperoleh beberapa informasi mengenai manajemen pemberian pakan dan pemeliharaan secara umum serta konsumsi pakan. Peubah dalam penelitian ini yakni kolesterol kuning telur sebagai peubah utama, pemberian pakan dan kualitas pakan sebagai peubah pendukung, Kandungan nutrisi pakan dianalisa secara proksimat. Kolesterol kuning telur beberapa peternakan ayam ras petelur di Pulau Ambon adalah 547,41 mg/100g pada Desa Suli, 543,26 mg/100g pada Dusun Hulung, dan 539,91 mg/100g pada Dusun Taeno. Berdasarkan hasil penelitian disimpulkan bahwa kadar kolesterol kuning telur ayam ras yang terendah ditemukan pada peternakan ayam dusun Taeno sebesar 539,909mg/100g. Kata kunci: Ayam ras petelur; Kolesterol; Kuning telur